Community Structure of Echinodermata in Juanga Village Water, Morotai Island Regency - Nurafni Nurafni; Sandra Hi Muhammad; Isman Dohu (Faculty of Agriculture Musamus University, 2020)
Echinoderms are animals that are included invertebrates that have thorny skin. The aim of this study was to analyze the structure of the Echinodermata community in Juanga coastal waters, Morotai Island Regency. This research was conducted in November 2019 in the waters of Juanga Village, Morotai Island Regency. By using the quadratic transect method, the transect line is pulled perpendicular to the sea along 100m at low tide or near lowest tide, starting at zero (0) and 1x1m squared are placed at each 10 m distance along the transect that is considered to represent the location for which there are samplesEchinoderms . While the analysis of the data used is the density of species (D), species diversity (H), demination index (C), and evenness (E). The results found 14 types of Echinoderms that were scattered at the study site. The highest density analysis at station I was 0.53 ind/m² ( Holothuria atra ) and the lowest 0.02 ind/m² (Acanthaster planci). Station II with the highest value of 0.33 ind/m² (Holothuria atra) and the lowest type of Stichopus variegatus, Echinothrix calamaris, Ophiaracna affinis, Ophiocoma brevipes with 0.02 ind / m², station III the highest density is still from the type Holothuria atra (0.42 ind/m²), the lowest is the kind Acanthaster planci, Ophiaracna affinis, Ophiocoma brevipes with an average value of 0.02 ind/m². Analysis of community structure (H') of stations I to III is included in the medium category, dominance index (C) no species dominates while the evenness index (E) of species distribution is very evenly distributed in all research locations.